Neuerwerbungen : 1976. - Städtisches Kunstmuseum Bonn (Bonn : Städtisches Kunstmuseum Bonn, 1977)
Beuys, Joseph ; Erben, Josef ; Gaul, Winfred ; Gerz, Jochen ; Graubner, Gotthard ; Hermanns, Ernst ; Höhme, Gerhard ; Jochims, Raimer ; Nestler, Wolfgang ; Paeffgen, C.O. ; Palermo ; Polke, Sigmar ; Richter, Gerhard ; Sieverding, Katharina ; Thieler, Fred ; Trantenroth, A.D. ; etc.
Neuerwerbungen : 1976, Städtisches Kunstmuseum Bonn, 5.4. - 8.5.1977
boek